Minimally Invasive Spine Surgery Advances and Innovations - Perez-Cruet, Mick (IntechOpen, 2022)
This book illustrates some of the latest advances in minimally invasive surgical techniques and technology to treat a variety of spinal disorders. Written by some of the leading minimally invasive spine surgeons, this book teaches surgeons how to perform these procedures safely and effectively. The goal is to advance the field of spinal surgery and ultimately improve the lives of patients suffering from spinal disorders. The book reviews cervical, thoracic, and lumbar approaches.